1991
DOI: 10.1038/bjc.1991.100
|View full text |Cite
|
Sign up to set email alerts
|

c-erbB-2 protein overexpression in breast cancer is a risk factor in patients with involved and uninvolved lymph nodes

Abstract: Summary The c-erbB-2 gene is overexpressed in about 20% of human breast cancers. Four hundred and eighty-three cases previously examined by immunohistochemical staining for c-erbB-2 expression were analysed to assess the risk associated with the elevated protein expression. Oncoprotein expression was correlated with increasing tumour grade but not with oestrogen receptor status, nodal involvement, tumour size or age. There was an increased risk of relapse and death associated with c-erbB-2 expression irrespect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
108
1
9

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(126 citation statements)
references
References 24 publications
8
108
1
9
Order By: Relevance
“…Ovet-expression of c-erbB-2 protein, on the other hand, was strongly correlated with DFS and S in our patients. Although some earlier studies have failed to show an association between prognosis and overexpression of the c-erbB-2 protein detected by IHC (14,15,20), there is a gencral agreement among more recently published reports that overexpression of the c-erbB-2 gene product is related to poor survival in breast cancer (10)(11)(12)(13)(33)(34)(35)(36). Our results are consistent with this emerging consensus.…”
Section: Discussionsupporting
confidence: 82%
“…Ovet-expression of c-erbB-2 protein, on the other hand, was strongly correlated with DFS and S in our patients. Although some earlier studies have failed to show an association between prognosis and overexpression of the c-erbB-2 protein detected by IHC (14,15,20), there is a gencral agreement among more recently published reports that overexpression of the c-erbB-2 gene product is related to poor survival in breast cancer (10)(11)(12)(13)(33)(34)(35)(36). Our results are consistent with this emerging consensus.…”
Section: Discussionsupporting
confidence: 82%
“…Assessment of the copy number of the Her-2neu gene and its expression has evolved as an important prognostic indicator in breast, ovarian, and uterine cancers. [35][36][37][38][39] The characteristic rearrangement of RARA with the PML (promyelocytic leukemia) gene on 15q22 has proven to be integral in the diagnosis and treatment of acute promyelocytic leukemia. [40][41][42] Since the cytogenetic findings of the current study and a review of the literature indicated that the 17p11-13 region likely harbors an oncogene of etiologic importance in aneurysmal bone cyst, efforts to further characterize the critically involved 17p breakpoint were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Both in situ and invasive low-grade lesions express oestrogen and progesterone receptors, but are usually negative for oncoproteins (HER/neu and p53). High-grade lesions exhibit the reverse (Hitchcock et al, 1989;Gullick et al, 1991;Barnes et al, 1993;Millis et al, 1996;Ellis et al, 1999). Molecular genetic studies find that low-grade lesions often demonstrate 16q deletions, while high-grade lesions have allelic losses of more chromosomal areas frequently including 1p, 1q, 6q, 9p, 11p, 13q and 17q.…”
Section: Discussionmentioning
confidence: 99%